Analisis Kinerja Pegawai di Biro Humas dan Keprotokolan Sekretariat Daerah Provinsi Sumatera Utara - Susanti Rizkasari; Harso Kardhinata; Isnaini Isnaini (Mahesa Research Center, 2022)
The research objectives are: To analyze the performance of employees and the barriers in the Public Relations and Protocol Bureau of the Regional Secretariat of North Sumatra Province. This type of research is qualitative in accordance with the formulation and research objectives. The results of research on employee performance in the Public Relations and Protocol Bureau of the Regional Secretariat of North Sumatra Province. Showing that the performance in terms of quantity and quality has been going well, this shows that employees are capable of achieving performance. Performance in terms of discipline that the implementation of work discipline starting from the presence of electronic attendance, morning apples and the use of official uniforms, there are still employees who commit violations of work discipline, especially during working hours where it is not optimal to carry out obligations with indicators complying with the provisions of working hours. This can be seen from the presence of employees who do not comply with the provisions of working hours, such as employees who often do not come to work, enter and leave the agency not according to regulations and are often late for office. Performance in terms of initiative that in carrying out their duties, employees always help each other with co-workers in completing tasks without any orders from superiors. Performance in terms of responsibility that employees are able to complete tasks properly in accordance with the specified time but on the one hand the discipline of employee performance is still not optimal.